Ischemic Stroke–A Scientometric Analysis - Millenaar, Dominic; Ragoschke-Schumm, Andreas; Fehlmann, Tobias; Raible, Maximilian; Lochner, Piergiorgio; Böhm, Michael; Fassbender, Klaus; Keller, Andreas; Mahfoud, Felix; Ukena, Christian (Frontiers in Neurology, 2022)
Background: Stroke is the second leading cause of death world-wide. A comprehensive scientometric study regarding ischemic stroke research has not been performed yet. This study aims at investigating the global research output on ischemic stroke research. Methods: All 21,115 articles regarding ischemic stroke were retrieved from the Web-of-Science-Core-Collection and analyzed regarding regional differences, the authors’ sex, subtopics of stroke, as well as international research collaborations. Results: A total of 132 different countries participated, with the USA contributing most publications with 4614 (21.9%), followed by China with 3872 (18.3%), and Germany with 1120 (5.3%). Analyzing the scientific quality of different countries by H-index, the USA ranked first with an H-index of 202, followed by Germany (H-index 135) and the United Kingdom (UK;H-index 129). The most frequently used topic was "Clinical Neurology" with 9028 publications. Among all first authors attributed to their sex, 32.3% of all first authors were female and 67.7% were male (4335 vs. 9097). The proportion of female last authors was comparatively lower at 22.4% (3083 publications) compared with 77.6% male authors (10,658 publications). There was a broad network of international collaborations. Conclusions: Research in ischemic stroke has significantly increased over time. Scientists from the USA have the highest number of publications, followed by China and Germany. Measured by the H-index, the USA held the highest publication quality, followed by Germany and the UK. The scientific landscape was male-dominated with 67.7% of all first authors being male. Worldwide international collaborations play a major role in ischemic stroke research.